2022
DOI: 10.1186/s12863-022-01050-0
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution detection of quantitative trait loci for seven important yield-related traits in wheat (Triticum aestivum L.) using a high-density SLAF-seq genetic map

Abstract: Background Yield-related traits including thousand grain weight (TGW), grain number per spike (GNS), grain width (GW), grain length (GL), plant height (PH), spike length (SL), and spikelet number per spike (SNS) are greatly associated with grain yield of wheat (Triticum aestivum L.). To detect quantitative trait loci (QTL) associated with them, 193 recombinant inbred lines derived from two elite winter wheat varieties Chuanmai42 and Chuanmai39 were employed to perform QTL mapping in six/eight e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…For TW, six QTLs were identified on the 1A, 1B, 6A, and 7D chromosomes. Some QTLs were also identified in previous reports on the 1A [ 30 , 57 ], 6A [ 55 , 58 ], and 7D [ 29 , 30 , 46 ] chromosomes, at different positions.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…For TW, six QTLs were identified on the 1A, 1B, 6A, and 7D chromosomes. Some QTLs were also identified in previous reports on the 1A [ 30 , 57 ], 6A [ 55 , 58 ], and 7D [ 29 , 30 , 46 ] chromosomes, at different positions.…”
Section: Discussionsupporting
confidence: 64%
“…The highest number of 12 QTLs were identified for PH on the 1B, 2B, 3A, 3B, 3D, 4A, 5A, 5D, 7B, and 7D chromosomes. Plant height is one of the important yield component traits in wheat, and therefore many QTLs were also identified in previous reports on chromosomes 1B [ 10 , 19 , 37 , 40 , 51 ], 2B [ 10 , 40 , 45 , 51 , 53 ], 3A [ 26 , 54 ], 3B [ 10 , 19 , 22 , 40 ], 4A [ 26 , 45 , 52 , 53 ], 5A [ 19 , 26 , 45 , 51 , 53 , 55 , 56 ], and 7B [ 10 ], at different positions. In addition, Alemu et al [ 52 ] identified a QTL on the 4A chromosome at 41cM, which was similar to that of QPH-4A and mapped at 41cM, explaining a 4.58% phenotypic variation.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…genome-wide association studies (GWAS) and quantitative trait loci (QTL) mapping are widely used methods to dissect the genetic basis of complex quantitative traits in crop plants. In the past decade, extensive efforts have been made to identify QTLs associated with grain yield and its component traits (Gao et al, 2015;Zhang et al, 2016;Jin et al, 2020;Isham et al, 2021;Kang et al, 2021;Li et al, 2022) in wheat through bi-parental populations based QTL mapping. Conventional QTL mapping mainly depends on structured populations like recombinant inbred lines (RIL), back-crosses (BC), and doubled haploids (DH).…”
Section: Introductionmentioning
confidence: 99%
“…Two main approaches to dissect the genetic basis of complex quantitative traits in crop plants are genome-wide association studies (GWAS) and quantitative trait loci (QTL) mapping. Many QTLs associated with yield-related traits in bread wheat have been identified in biparental populations (Gao et al 2015;Yu et al 2017;Milner et al, 2016;Zhang et al 2016;Jin et al 2020;Isham et al 2021;Kang et al 2021;Li et al 2022). At present, GWAS has become more frequently used as it allows to identify of parts of the complex, essential traits valid in a studied panel of genotypes (Breseghello and Sorrells 2006;Neumann et al 2011;Dodig et al 2012;Jiang et al 2015;Liu et al 2015;Hu et al 2015;Sukumaran et al 2015;Sukumaran et al 2018;Tadesse et al 2015;Lozada et al 2017;Sun et al 2017;Würschum et al 2017b;Bhatta et al 2018;Sheoran et al 2019;Sun et al 2017;Liu et al 2018;Akram et al 2021;Qaseem et al 2019;Garcia et al 2019).…”
Section: Introductionmentioning
confidence: 99%